2012
DOI: 10.1111/j.1600-6143.2012.04244.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life on Home Parenteral Nutrition and After Intestinal Transplantation Using Treatment-Specific Questionnaires

Abstract: In order to investigate the quality of life on home parenteral nutrition and after intestinal transplantation using comparable questionnaires, the treatmentspecific quality of life questionnaire for adult patients on home parenteral nutrition was adapted for intestinal transplant recipients. Both instruments were composed of 8 functional scales, 9 symptom scales, 3 global health status/quality of life scales and 2 single items. A preliminary cross-sectional study enrolling all the patients currently cared at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 16 publications
1
46
0
1
Order By: Relevance
“…The age and gender distribution in our study are comparable to those of other surveys, which also showed a much higher rate of female HPN patients [4,[13][14][15] . This is influenced by the underlying diseases, for example, post-radiation enteritis occurring in patients with gynecological malignancies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The age and gender distribution in our study are comparable to those of other surveys, which also showed a much higher rate of female HPN patients [4,[13][14][15] . This is influenced by the underlying diseases, for example, post-radiation enteritis occurring in patients with gynecological malignancies.…”
Section: Discussionsupporting
confidence: 77%
“…Many other studies determined the QoL using the Karnofsky score, the SF-36 or a new specific questionnaire for HPN patients. Overall, patients with HPN have poorer QoL than healthy people or patients with chronic illnesses [13,19,[32][33][34] . An earlier study with only 13 participants showed that none of those HPN patients had a regular employment, but 46% did most of the housekeeping [35] .…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18,27 However, most patients do not escape the associated life-threatening complications including line sepsis, central venous thrombosis, and liver failure in addition to other significant metabolic and psychosocial derangements. 17,27,40 According to different North American and European studies, patients with diagnosis of CD represent nearly one-third of the HPN population excluding those with cancer and AIDS. [16][17][18]41 With variable HPN-associated complication rates including higher incidence of recurrent line sepsis, the survival outcome of the HPN-dependent CD patients seems to be higher than those with other gut disorders with a minimum 5-year survival rate of 80%.…”
Section: Intestinal Failurementioning
confidence: 99%
“…Quality-of-life (QOL) has been demonstrated to be better after intestine transplantation compared to patients remaining on PN (56)(57)(58). In two studies of QOL after intestine transplantation, the presence of G-tubes or ostomies and repeat hospitalization were factors associated with decreased scores (56,58).…”
Section: Quality Of Lifementioning
confidence: 99%
“…In two studies of QOL after intestine transplantation, the presence of G-tubes or ostomies and repeat hospitalization were factors associated with decreased scores (56,58). The Pittsburgh group (57) compared QOL before and after intestine transplantation in 76 surviving adult recipients with mixed results.…”
Section: Quality Of Lifementioning
confidence: 99%